PELAKSANAAN PROGRAM PENGEMBANGAN OBJEK WISATA AIR TERJUN SIPISO-PISO OLEH DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KARO - Sitepu, Dani Rinaldi; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tourism is one of the utilization of natural resources that can be pf high economic value for a regination that manage natural resources into a tourist spot that can attract visitors both from within and from abroard, in addition to econimic value is higt and can create jobs and encourage growth invesment, tourism can foster and enhance a sense of pride in the nation so that it wi grow more concerned about the people of a nation. This research is aims to determine the potential of which is owned by the attraction of Sipiso-piso waterfall and to describe the develoment as well as factors inhibiting and supporting the imlpementation of tourism develoment Sipio-piso Waterfall by Departement of Cultural and Tourism Karo.This study used a qualitative research method with descriptive data analysis. This concept of using tke teory of develoment tourism theory. In collecting data, the researcher used interview, observation, and documentation. By using key informants as a source of information and triangulation techniques as a sourch in view of data validation.The results of the research is implementation of develoment tourist attraction of Sipiso-piso Waterfall in district Karo has not been ralized with good. Because inhibiting factors imlpementation tourism develoment of Devertement of Cultural and Tourism Karo by natural actor and the lack of participation.Key Word: Tourism develoment, Tourist Attraction, Program